Flora of Bahia – Bignoniaceae 1: Jacaranda Jussieu - Silva-Castro, Milene Maria da; Agustinho, Cibele R. de; Brito, Rafael F. (SITIENTIBUS série Ciências Biológicas, 2007)
This work aims at surveying the species of Jacaranda Juss. (Bignoniaceae) in the state of Bahia, Brazil. Collections in the following herbaria were studied: ALCB (Universidade Federal da Bahia), CEPEC (Centro de Pesquisa do Cacau), HRB (IBGE – RadamBrasil), HUEFS (Herbário da Universidade Estadual de Feira de Santana) and HUESB (Herbário da Universidade Estadual do Sudoeste da Bahia - Jequié). Fifteen species were found: Jacaranda bracteata Bur. and K. Schum., J. brasiliana (Lam.) Pers., J. caroba (Vell.) DC., J. duckei Vatt., J. grandifoliolata A. Gentry, J. aff grandifoliolata A. Gentry, J. irwinii A. Gentry, J. jasminoides (Thunb.) Sandw., J. microcalyx A. Gentry, J. obovata Cham., J. aucifoliolata Mart. ex DC., J. praetermissa Sandw., J. puberula Cham., J. simplicifolia K. Schum. ex Bur. and K. Schum., and J. ulei Bur. and K. Schum. Key, descriptions, illustrations and comments on geographical distribution, phenology and morphological variability are presented to these species.